Hyaluronan in COVID-19: a matrix for understanding lung disease - Rebecca J. Dodd; Judith E. Allen; Anthony J. Day (mBio)
ABSTRACT The polysaccharide hyaluronan (HA) is an important component of lung extracellular matrix that increases following infection with influenza or severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Hellman et al. (U. Hellman, E. Rosendal, J. Lehrstrand, J. Henriksson, et al., mBio 15:e01303-24, https://doi.org/10.1128/mbio.01303-24) show that fragmented HA accumulates in the lungs of coronavirus disease 2019 (COVID-19) patients, with systemic levels of HA being associated with reduced lung function 3–6 months after infection. This study provides novel insights into HA’s role in COVID-19 pathology and its potential utility as a biomarker for disease severity. However, much remains to be understood about the lung HA matrix in COVID-19 and how it compares to other lung conditions. In particular, the role of HA-binding proteins in organizing HA into a crosslinked network is yet to be fully determined at a molecular level. This knowledge is crucial in understanding the inter-relationships between the structure of the HA matrix and the regulation of the immune response, and thus our ability to target HA therapeutically for improved outcomes in COVID-19.